Post a New Question


posted by .

how do I solve this problem 2x/2=(6-3y)/2?

I solved it for you in my initial answer.
The 2 in the numerator cancels with the 2 in the denominator on th left side and
x = (6-3y)/2

which is the solution of the initial equation you had for x in terms of y.
You CAN divide 2 into both 6 and -3y on the right if you wish to give
x = (6/2) - (3y)/2 = 3 - (3y)/2

Answer This Question

First Name
School Subject
Your Answer

Related Questions

More Related Questions

Post a New Question